Radial force distribution changes associated with tangential force production in cylindrical grasping, and the importance of anatomical registration - Pataky, Todd C.; Slota, Gregory P.; Latash, Mark L.; Zatsiorsky, Vladimir M. (Journal of biomechanics, 2012)
Radial force (Fr) distributions describe grip force coordination about a cylindrical object. Recent studies have employed only explicit Fr tasks, and have not normalized for anatomical variance when considering Fr distributions. The goals of the present study were (i) to explore Fr during tangential force production tasks, and (ii) to examine the extent to which anatomical registration (i.e. spatial normalization of anatomically analogous structures) could improve signal detectability in Fr data. Twelve subjects grasped a vertically oriented cylindrical handle (diameter=6cm) and matched target upward tangential forces of 10, 20, and 30N. Fr data were measured using a flexible pressure mat with an angular resolution of 4.8°, and were registered using piecewise-linear interpolation between five manually identified points-of-interest. Results indicate that Fr was primarily limited to three contact regions: the distal thumb, the distal fingers, and the fingers’ metatacarpal heads, and that, while increases in tangential force caused significant increases in Fr for these regions, they did not significantly affect the Fr distribution across the hand. Registration was found to substantially reduce between-subject variability, as indicated by both accentuated Fr trends, and amplification of the test statistic. These results imply that, while subjects focus Fr primarily on three anatomical regions during cylindrical grasp, inter-subject anatomical differences introduce a variability that, if not corrected for via registration, may compromise one's ability to draw anatomically relevant conclusions from grasping force data.